Enterocolite Necrosante: avaliação entre os fatores de risco e de proteção com a gravidade e o desfecho da doença - Marcondes, Maria Raquel Alvarenga (2019)
Background: The Necrotizing Enterocolitis (NEC) is the most serious systemic gastrointestinal and systemic disease affecting newborns (NB), especially in neonatal units, with high mortality rates among patients. It is also neonatal disease with more surgical indications and severe outcomes, such as short bowel syndrome and long-term psychomotor disorders. During the last decades, much has been investigated on the cause, diagnosis, symptoms, prognosis, treatment, complications and prevention of the disease. However, there is still no complete understanding about the cause, pathogenesis, prevention or treatment of NEC. Several factors of stress faced by the newborn during gestation or in the postnatal period are related to the cause of the disease, but prematurity has been cited as the main causal factor. The identification of risk factors and prenatal and neonatal protection related to the more advanced stages of the disease can contribute to the prevention of worse outcomes and complications. Purpose: Relate prenatal and neonatal risk and protection factors to neonatal severity and outcome of NEC. Material and Methods: A retrospective observational study was conducted in which 88 NB (preterm and term), diagnosed with NEC, admitted to a university hospital in the state of Minas Gerais/Brazil, were enrolled in the period of January 1, 2007 to December 31, 2016 (10 retrospective years) and their respective mothers. A datasheet was developed for annotations of the main prenatal risk factors, neonatal and complications related to NEC. The disease was classified according to the criteria of Bell et al. (1978), which considers three stages of severity. Results: 88 NBs diagnosed with NEC were considered eligible, of which 11 were excluded. Of the 77 cases evaluated, 79.22% were preterm infants and 20.78% were term infants. Regarding severity, 40.25% belonged to stage I, 24.67% to stage II and, 35.06% to stage III of the disease. The present study also found that the severity of NEC manifestations were related, in particular, to the time of oxygen therapy and mechanical ventilation, the presence of early sepsis and the use of gastric mucosal protective drugs, which are also related to the RN clinical severity of the disease itself, according to the SNAPPE-II score. Although the results did not show a relation between the use of illicit and licit drugs by pregnant women and the severity of NEC, the highest number of mothers using illicit drugs was reported in the group of NBs classified in stage III of the disease. It was also possible to observe that the risk for death was related to the time of mechanical ventilation, early sepsis, hypoglycemia and the most severe stages of NEC. In addition, the results suggest that human milk was a protective factor for the development of more severe stages of the disease. Regarding the therapeutic conduct (management) in the different stages of NEC, a greater number of surgical cases were observed in stage III, consequently the presence of short bowel syndrome. Conclusion: The risk factors related to its severity were the time of oxygen therapy and mechanical ventilation, the presence of early sepsis and the use of gastric mucosal protective drugs, an analogous situation was evidenced to the clinical severity of the newborn, according to the SNAPPE-II score . It is also concluded that mechanical ventilation(p=0,049) and the presence of early sepsis(p=0,014) may also influence the outcome (death), as well as hypoglycemia(p=0,047) and more severe forms of NEC (stage III versus I - odds ratio of 5.4 and p-value = 0.010). In addition, the possible protective role of human milk for the development of the most severe stages of NEC was observed.